Surface transport in the single market report of the seminar held on 25 March 1993 to mark the publication of the Infrastructure Policy Group report Infrastructure - the challenge of '92. (Thomas Telford, 1993)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Report on a seminar held on 25 March 1993.